Optimalisasi Potensi Lokal oleh Bumdes Berkarya dalam Pengembangan Desa Wisata Wonorejo, Kabupaten Karanganyar - Hanin Kaulika Ulma; Vidya Imanuari Pertiwi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to identify, analyze, and describe the development of the tourist village through the utilization of local potential by BUMDes Berkarya in Wonorejo Tourist Village, Jatiyoso District, Karanganyar Regency. This study uses descriptive research methods with a qualitative approach, employing data collection techniques such as observation, interviews, and documentation. The theory used in this research involves tourism destination elements consisting of five focuses: tourist attractions, attractions, tourist facilities and general facilities, accessibility, and brand images. The results of this research indicate that the development of the tourist village through the utilization of local potential by BUMDes Berkarya in Wonorejo Tourist Village is quite good and aligns with existing theories. However, there are still some shortcomings that need to be improved and further developed, such as incorporating local culture as an attraction, adding facilities, and improving accessibility to facilitate easier access. These improvements aim to achieve the goal of tourism development, which is to attract tourist visits and enhance community welfare.